INFORMED LOCAL COMMUNITIES ACT AS CATALYSTS FOR TOURISM DEVELOPMENT: EVIDENCE FROM RURAL INDIA - Millo Yaja; Anuj Kumar; Millo Mamung; Bindu Roy (Tourism and Hospitality Management, 2024)
Purpose – The level of tourism development in any destination is directly related to the cooperation of the local community, and this is especially true in rural areas in many parts of the world. Many governments initiate development programs related to tourism in rural areas to provide new opportunities for local communities. However, most local communities are unaware of these opportunities. This study therefore examined how tourism forums influence awareness and perceptions of tourism development. Design/Methodology – Data were collected from local tourism entrepreneurs using a structured questionnaire. Tourism entrepreneurs in this study include host families, hotels, gift stores, and transportation entrepreneurs from the rural region. Findings – The results indicate that there are significant differences in perceptions of tourism development between those who attend the forum(s) and those who do not. Furthermore, these differences vary between different types of tourism service providers. Perceptions of tourism service providers are influenced by their knowledge of tourism programs and their participation in public forums. Originality – All respondents in this study were first generation entrepreneurs, which in itself makes this study unique. The fact that tourism forum(s) act as a platform to eliminate misunderstandings between authorities and local communities has not been highlighted and distinguished in previous studies, which makes this study an original contribution.